Single-phase power line conditioning with unity power factor under distorted utility voltage. (October 2020) - Castellan, Simone; Buja, Giuseppe; Menis, Roberto
Highlights: Novel proposed approach for power factor correction of single-phase loads. Effectiveness of the compensation also when the utility voltage is distorted. Control algorithm based on the single phase p-q theory and using TOSSI filters. Achievement of unity power factor rather than sinusoidal utility current. Effectiveness of the approach is corroborated by hardware-in-the-loop tests. Abstract: The paper proposes a control method of a single-phase active power line conditioner (APLC) aimed at correcting the power factor of linear and non-linear loads supplied by distorted voltage utility. The method, that is based on the single-phase p-q theory and utilizes a third-order sinusoidal signal integrator, gets utility unity power factor and, at the same time, overcomes the shortcomings of the solutions pursuing utility sinusoidal current, namely the possible onset of un-damped resonance phenomena and the reduction in the energy delivery capabilities; moreover, the method makes the power factor correction robust against the supply distortion. The excellent performance of the method is substantiated by testing it by means of a hardware-in-the-loop setup.